A multi-scale analysis of drought effects on intrinsic water use efficiency in a Mediterranean evergreen oak forest - Serge Rambal; Jeannine Cavender-Bares; Jean-Marc Limousin; Yann Salmon (Agricultural and Forest Meteorology, 2025)

Rainfall manipulation experiments as simulated by terrestrial biosphere models: Where do we stand? - Athanasios Paschalis; Simone Fatichi; Jakob Zscheischler; Philippe Ciais; Michael Bahn; Lena Boysen; Jinfeng Chang; Martin De Kauwe; Marc Estiarte; Daniel Goll; Paul J. Hanson; Anna B. Harper; et al. (Global Change Biology, 2020)
Changes in rainfall amounts and patterns have been observed and are expected to continue in the near future with potentially significant ecological and societal consequences. Modelling vegetation responses to changes in rainfall is thus crucial to project water and carbon cycles in the future. In this study, we present the results of a new model‐data intercomparison project, where we tested the ability of 10 terrestrial biosphere models to reproduce the observed sensitivity of ecosystem productivity to rainfall changes at 10 sites across the globe, in nine of which, rainfall exclusion and/or irrigation experiments had been performed. The key results are as follows: (a) Inter‐model variation is generally large and model agreement varies with timescales. In severely water‐limited sites, models only agree on the interannual variability of evapotranspiration and to a smaller extent on gross primary productivity. In more mesic sites, model agreement for both water and carbon fluxes is typically higher on fine (daily–monthly) timescales and reduces on longer (seasonal–annual) scales. (b) Models on average overestimate the relationship between ecosystem productivity and mean rainfall amounts across sites (in space) and have a low capacity in reproducing the temporal (interannual) sensitivity of vegetation productivity to annual rainfall at a given site, even though observation uncertainty is comparable to inter‐model variability. (c) Most models reproduced the sign of the observed patterns in productivity changes in rainfall manipulation experiments but had a low capacity in reproducing the observed magnitude of productivity changes. Models better reproduced the observed productivity responses due to rainfall exclusion than addition. (d) All models attribute ecosystem productivity changes to the intensity of vegetation stress and peak leaf area, whereas the impact of the change in growing season length is negligible. The relative contribution of the peak leaf area and vegetation stress intensity was highly variable among models.

Recent climate hiatus revealed dual control by temperature and drought on the stem growth of Mediterranean Quercus ilex - Morine Lempereur; Jean‐Marc Limousin; Frédéric Guibal; Jean‐Marc Ourcival; Serge Rambal; Julien Ruffault; Florent Mouillot (Global Change Biology, 2017)
A better understanding of stem growth phenology and its climate drivers would improve projections of the impact of climate change on forest productivity. Under a Mediterranean climate, tree growth is primarily limited by soil water availability during summer, but cold temperatures in winter also prevent tree growth in evergreen forests. In the widespread Mediterranean evergreen tree species Quercus ilex , the duration of stem growth has been shown to predict annual stem increment, and to be limited by winter temperatures on the one hand, and by the summer drought onset on the other hand. We tested how these climatic controls of Q. ilex growth varied with recent climate change by correlating a 40‐year tree ring record and a 30‐year annual diameter inventory against winter temperature, spring precipitation, and simulated growth duration. Our results showed that growth duration was the best predictor of annual tree growth. We predicted that recent climate changes have resulted in earlier growth onset (−10 days) due to winter warming and earlier growth cessation (−26 days) due to earlier drought onset. These climatic trends partly offset one another, as we observed no significant trend of change in tree growth between 1968 and 2008. A moving‐window correlation analysis revealed that in the past, Q. ilex growth was only correlated with water availability, but that since the 2000s, growth suddenly became correlated with winter temperature in addition to spring drought. This change in the climate–growth correlations matches the start of the recent atmospheric warming pause also known as the ‘climate hiatus’. The duration of growth of Q. ilex is thus shortened because winter warming has stopped compensating for increasing drought in the last decade. Decoupled trends in precipitation and temperature, a neglected aspect of climate change, might reduce forest productivity through phenological constraints and have more consequences than climate warming alone.

Combined effects of climate, resource availability, and plant traits on biomass produced in a Mediterranean rangeland - Simon Chollet; Serge Rambal; Adeline Fayolle; Daniel Hubert; Didier Foulquié; Eric Garnier (Ecology, 2014)
Biomass production in grasslands, a key component of food provision for domestic herbivores, is known to depend on climate, resource availability, and on the functional characteristics of communities. However, the combined effects of these different factors remain largely unknown. The aim of the present study was to unravel the causes of variations in the standing biomass of plant communities using a long‐term experiment conducted in a Mediterranean rangeland of Southern France. Two management regimes, sheep grazing and grazing associated with mineral fertilization, were applied to different areas of the study site over the past 25 years. Abiotic (temperature, available water, nutrients) and biotic (components of the functional structure communities) factors were considered to explain interannual and spatial variations in standing biomass in these rangelands. Standing biomass was highly predictable, with the best model explaining ∼80% of variations in the amount of biomass produced, but the variation explained by abiotic and biotic factors was dependent on the season and on the management regime. Abiotic factors were found to have comparable effects in both management regimes: The amount of biomass produced in the spring was limited by cold temperatures, while it was limited by water availability and high temperatures in the summer. In the fertilized community, the progressive change in the functional structure of the communities had significant effects on the amount of biomass produced: the dominance of few productive species which were functionally close led to higher peak standing biomass in spring.

Ectomycorrhizal fungal diversity in Quercus ilex Mediterranean woodlands: variation among sites and over soil depth profiles in hyphal exploration types, species richness and community composition - Oula Shahin; Nicolas Martin-St Paul; Serge Rambal; Richard Joffre; Franck Richard (Symbiosis, 2013)

Change in water loss regulation after canopy clearcut of a dominant shrub in Sahelian agrosystems, Guiera senegalensis J. F. Gmel - Hassane Bil-Assanou Issoufou; Sylvain Delzon; Jean-Paul Laurent; Mahamane Saâdou; Ali Mahamane; Bernard Cappelaere; Jérôme Demarty; Monique Oï; Serge Rambal; Josiane Seghieri (Trees, 2013)

Drought Influences the Accuracy of Simulated Ecosystem Fluxes: A Model-Data Meta-analysis for Mediterranean Oak Woodlands - Rodrigo Vargas; Oliver Sonnentag; Gab Abramowitz; Arnaud Carrara; Jing Ming Chen; Philippe Ciais; Alexandra Correia; Trevor F. Keenan; Hideki Kobayashi; Jean-Marc Ourcival; Dario Papale; David Pearson; et al. (Ecosystems, 2013)

The temporal response to drought in a Mediterranean evergreen tree: comparing a regional precipitation gradient and a throughfall exclusion experiment - Nicolas K. Martin‐StPaul; Jean‐Marc Limousin; Hélène Vogt‐Schilb; Jesus Rodríguez‐Calcerrada; Serge Rambal; Damien Longepierre; Laurent Misson (Global Change Biology, 2013)
Like many midlatitude ecosystems, Mediterranean forests will suffer longer and more intense droughts with the ongoing climate change. The responses to drought in long‐lived trees differ depending on the time scale considered, and short‐term responses are currently better understood than longer term acclimation. We assessed the temporal changes in trees facing a chronic reduction in water availability by comparing leaf‐scale physiological traits, branch‐scale hydraulic traits, and stand‐scale biomass partitioning in the evergreen Q uercus ilex across a regional precipitation gradient (long‐term changes) and in a partial throughfall exclusion experiment ( TEE , medium term changes). At the leaf scale, gas exchange, mass per unit area and nitrogen concentration showed homeostatic responses to drought as they did not change among the sites of the precipitation gradient or in the experimental treatments of the TEE . A similar homeostatic response was observed for the xylem vulnerability to cavitation at the branch scale. In contrast, the ratio of leaf area over sapwood area ( LA / SA ) in young branches exhibited a transient response to drought because it decreased in response to the TEE the first 4 years of treatment, but did not change among the sites of the gradient. At the stand scale, leaf area index ( LAI ) decreased, and the ratios of stem SA to LAI and of fine root area to LAI both increased in trees subjected to throughfall exclusion and from the wettest to the driest site of the gradient. Taken together, these results suggest that acclimation to chronic drought in long‐lived Q . ilex is mediated by changes in hydraulic allometry that shift progressively from low (branch) to high (stand) organizational levels, and act to maintain the leaf water potential within the range of xylem hydraulic function and leaf photosynthetic assimilation.

Differential regional responses in drought length, intensity and timing to recent climate changes in a Mediterranean forested ecosystem - Julien Ruffault; Nicolas K. Martin-StPaul; Serge Rambal; Florent Mouillot (Climatic Change, 2013)

Morphological and phenological shoot plasticity in a Mediterranean evergreen oak facing long-term increased drought - Jean-Marc Limousin; Serge Rambal; Jean-Marc Ourcival; Jesus Rodríguez-Calcerrada; Ignacio M. Pérez-Ramos; Raquel Rodríguez-Cortina; Laurent Misson; Richard Joffre (Oecologia, 2012)

Long-term physiological and morphological acclimation by the evergreen shrub Buxus sempervirens L. to understory and canopy gap light intensities - Matthew G. Letts; Jesús Rodríguez-Calcerrada; Víctor Rolo; Serge Rambal (Trees, 2012)

Seasonal hysteresis of net ecosystem exchange in response to temperature change: patterns and causes - SHULI NIU; YIQI LUO; SHENFENG FEI; LEONARDO MONTAGNANI; GIL BOHRER; IVAN A. JANSSENS; BERT GIELEN; SERGE RAMBAL; EDDY MOORS; GIORGIO MATTEUCCI (Global Change Biology, 2011)
Understanding how net ecosystem exchange (NEE) changes with temperature is central to the debate on climate change‐carbon cycle feedbacks, but still remains unclear. Here, we used eddy covariance measurements of NEE from 20 FLUXNET sites (203 site‐years of data) in mid‐ and high‐latitude forests to investigate the temperature response of NEE. Years were divided into two half thermal years (increasing temperature in spring and decreasing temperature in autumn) using the maximum daily mean temperature. We observed a parabolic‐like pattern of NEE in response to temperature change in both the spring and autumn half thermal years. However, at similar temperatures, NEE was considerably depressed during the decreasing temperature season as compared with the increasing temperature season, inducing a counter‐clockwise hysteresis pattern in the NEE–temperature relation at most sites. The magnitude of this hysteresis was attributable mostly (68%) to gross primary production (GPP) differences but little (8%) to ecosystem respiration (ER) differences between the two half thermal years. The main environmental factors contributing to the hysteresis responses of NEE and GPP were daily accumulated radiation. Soil water content (SWC) also contributed to the hysteresis response of GPP but only at some sites. Shorter day length, lower light intensity, lower SWC and reduced photosynthetic capacity may all have contributed to the depressed GPP and net carbon uptake during the decreasing temperature seasons. The resultant hysteresis loop is an important indicator of the existence of limiting factors. As such, the role of radiation, LAI and SWC should be considered when modeling the dynamics of carbon cycling in response to temperature change.

Phenological responses to extreme droughts in a Mediterranean forest - LAURENT MISSON; DAVID DEGUELDRE; CHRISTIAN COLLIN; RAQUEL RODRIGUEZ; ALAIN ROCHETEAU; JEAN‐MARC OURCIVAL; SERGE RAMBAL (Global Change Biology, 2011)
Mediterranean regions are projected to experience more frequent, prolonged and severe drought as a consequence of climate change. We used a retractable rainfall shelter, to investigate the impact of extreme droughts on the development of Quercus ilex leaves, flowers and fruit. In 2008, 97% of rainfall was excluded from a forest plot during the autumn, representing 50% of the 1127 mm of rain that fell during the year. In 2009, 87% of rainfall was excluded during the spring, representing 58% of the 749 mm that fell during the year. The rainfall shelter did not impact neither incident radiation nor air temperature. Autumn rainfall exclusion did not significantly affect leaf, flowers or fruit development. Spring rainfall exclusion resulted in larger and more sustained depression of leaf water potential during the key phases of foliar and floral development. Consequently, only half of the sampled trees (6) reached the shoot lengthening stage which leads to functionally mature leaves (phenophase 4), with one abandoning leaf development at budburst (phenophase 3) and the other two at the bud swelling stage (phenophase 2). All trees of the control plot passed phenophase 4, with most reaching complete leaf development. The impact of extreme droughts on flower development differed between the sexes. The spring exclusion had no effect on male flower, but only one of six trees completed female fruit maturation, compared with four in the control plot. The difference between the male and female drought impacts is likely attributable to the occurrence of male floral development before the period of lowest leaf water potential, and to the lower resource allocation requirements of male flowers. The information provided by our experimental approach may constitute a crucial step to evaluate the impact of increasing drought due to climate change on the most dominant Mediterranean tree species and to help drawing a full picture of the ecological consequences of the decline in water resource on forest dynamics under changing conditions.

Identification of vegetation and soil carbon pools out of equilibrium in a process model via eddy covariance and biometric constraints - NUNO CARVALHAIS; MARKUS REICHSTEIN; PHILIPPE CIAIS; G. JAMES COLLATZ; MIGUEL D. MAHECHA; LEONARDO MONTAGNANI; DARIO PAPALE; SERGE RAMBAL; JÚLIA SEIXAS (Global Change Biology, 2010)
Assumptions of steady‐state conditions in biogeochemical modelling are often invoked because knowledge on the development status of the modelling domain is generally unavailable. Here, we investigate the role of vegetation pool sizes on nonequilibrium conditions through model‐data integration approaches for a set of sites using eddy covariance CO 2 flux data. The study is based on the Carnegie–Ames–Stanford Approach (CASA) model, modified (CASA G ) in order to evaluate the sensitivity of simulated net ecosystem production (NEP) fluxes to vegetation pool sizes. The experimental design is based on the inverse model optimization of different parameter vectors performed at the measurement site level. Each parameter vector prescribes different simulation dynamics that embody different model structural assumptions concerning (non)steady‐state conditions in vegetation and soil carbon pools. We further explore the potential of assimilating biometric constraints through the cost function for sites where in situ information on aboveground biomass or wood pools is available. The integration of biometric data yields marked improvements in the simulation of vegetation C pools compared to single constraints with eddy flux data. Overall, it is necessary to relax both vegetation and soil carbon pools for consistency with the observed data streams. Multiple constraints approaches also leads to variable model performance among the different experimental setups and model structures. We identify and assess the limitations of various model structures and the role of multiple constraints approaches for tackling issues of equifinality. These studies emphasize the need for establishing consistent data sets of fluxes and biometric data for successful model‐data fusion.

Functional changes in the control of carbon fluxes after 3 years of increased drought in a Mediterranean evergreen forest? - LAURENT MISSON; ALAIN ROCHETEAU; SERGE RAMBAL; JEAN‐MARC OURCIVAL; JEAN‐MARC LIMOUSIN; RAQUEL RODRIGUEZ (Global Change Biology, 2010)
Our objective was to test how a long‐term increased water limitation affects structural and functional properties of a Mediterranean ecosystem, and how these changes modify the response of the main carbon fluxes to climatic controls. In 2003, a 27% throughfall exclusion experiment was installed in a Quercus ilex L. forest in France. Gross primary production (GPP), ecosystem respiration ( R ECO ) and net ecosystem exchange (NEE) were estimated in a control and a dry treatment. Decreasing throughfall decreased GPP by 14% and had a smaller effect on R ECO (−12%), especially soil respiration R S (−11%). Interannual variability of GPP (29%) was higher than for R ECO (12%). Error propagation was used to estimates uncertainties in the NEE fluxes, which ranged from 3% to 10% in the control treatment but up to 167% for NEE in the dry treatment because more steps and data types were involved in the scaling. After 3 years of throughfall exclusion, we found no acclimation of R S to climatic drivers. Functional properties of the response of R S to soil water, temperature and rain pulse remained similar in the control and the dry treatments. A diurnal clockwise hysteresis in R S was probably controlled by canopy photosynthesis with a 3 h lag. The proportion of diurnal variation of respiration due to photosynthesis was similar in all treatments (4–5%). Because of the characteristic of rain in Mediterranean climates, a continuous decrease of water input in these environments have an effect on topsoil water and consequently on R S only during short periods when rainfall is characterized by infrequent and small events that does not allow the topsoil to reach field capacity and does not allow to dry completely. However, in the longer term, we expect a stronger decrease in R S in the dry treatment driven by the decrease in GPP.

Modelling the drought impact on monoterpene fluxes from an evergreen Mediterranean forest canopy - Rüdiger Grote; Anne-Violette Lavoir; Serge Rambal; Michael Staudt; Ina Zimmer; Jörg-Peter Schnitzler (Oecologia, 2009)

On the separation of net ecosystem exchange into assimilation and ecosystem respiration: review and improved algorithm - Markus Reichstein; Eva Falge; Dennis Baldocchi; Dario Papale; Marc Aubinet; Paul Berbigier; Christian Bernhofer; Nina Buchmann; Tagir Gilmanov; André Granier; Thomas Grünwald; Katka Havránková; et al. (Global Change Biology, 2005)
This paper discusses the advantages and disadvantages of the different methods that separate net ecosystem exchange (NEE) into its major components, gross ecosystem carbon uptake (GEP) and ecosystem respiration ( R eco ). In particular, we analyse the effect of the extrapolation of night‐time values of ecosystem respiration into the daytime; this is usually done with a temperature response function that is derived from long‐term data sets. For this analysis, we used 16 one‐year‐long data sets of carbon dioxide exchange measurements from European and US‐American eddy covariance networks. These sites span from the boreal to Mediterranean climates, and include deciduous and evergreen forest, scrubland and crop ecosystems. We show that the temperature sensitivity of R eco , derived from long‐term (annual) data sets, does not reflect the short‐term temperature sensitivity that is effective when extrapolating from night‐ to daytime. Specifically, in summer active ecosystems the long‐term temperature sensitivity exceeds the short‐term sensitivity. Thus, in those ecosystems, the application of a long‐term temperature sensitivity to the extrapolation of respiration from night to day leads to a systematic overestimation of ecosystem respiration from half‐hourly to annual time‐scales, which can reach >25% for an annual budget and which consequently affects estimates of GEP. Conversely, in summer passive (Mediterranean) ecosystems, the long‐term temperature sensitivity is lower than the short‐term temperature sensitivity resulting in underestimation of annual sums of respiration. We introduce a new generic algorithm that derives a short‐term temperature sensitivity of R eco from eddy covariance data that applies this to the extrapolation from night‐ to daytime, and that further performs a filling of data gaps that exploits both, the covariance between fluxes and meteorological drivers and the temporal structure of the fluxes. While this algorithm should give less biased estimates of GEP and R eco , we discuss the remaining biases and recommend that eddy covariance measurements are still backed by ancillary flux measurements that can reduce the uncertainties inherent in the eddy covariance data.

Drought controls over conductance and assimilation of a Mediterranean evergreen ecosystem: scaling from leaf to canopy - Serge Rambal; Jean‐Marc Ourcival; Richard Joffre; Florent Mouillot; Yann Nouvellon; Markus Reichstein; Alain Rocheteau (Global Change Biology, 2003)
Drought control over conductance and assimilation was assessed using eddy flux and meteorological data monitored during four summer periods from 1998 to 2001 above a closed canopy of the Mediterranean evergreen oak tree Quercus ilex . Additional discrete measurements of soil water content and predawn leaf water potential were used to characterize the severity of the drought. Canopy conductance was estimated through the big‐leaf approach of Penman–Monteith by inverting latent heat fluxes. The gross primary production ( GPP ) was estimated by adding ecosystem respiration to net ecosystem exchange. Ecosystem respiration was deduced from night flux when friction velocity ( u * ) was greater than 0.35 m s −1 . Empirical equations were identified that related maximal canopy conductance and daily ecosystem GPP to relative soil water content ( RWC) , the ratio of current soil water content to the field capacity, and to the predawn leaf water potential. Both variables showed a strong decline with soil RWC for values lower than 0.7. The sharpest decline was observed for GPP . The curves reached zero for RWC =0.41 and 0.45 for conductance and GPP , respectively. When the predawn leaf water potential was used as a surrogate for soil water potential, both variables showed a hyperbolic decline with decreasing water potential. These results were compared with already published literature values obtained at leaf level from the same tree species. Scaling up from the leaf to ecosystem highlighted the limitation of two big‐leaf representations: Penman–Monteith and Sellers' Π factor. Neither held completely for comparing leaf and canopy fluxes. Tower measurements integrate fluxes from foliage elements clumped at several levels of organization: branch, tree, and ecosystem. The Q. ilex canopy exhibited non‐random distribution of foliage, emphasizing the need to take into account a clumping index, the factor necessary to apply the Lambert–Beer law to natural forests. Our results showed that drought is an important determinant in water losses and CO 2 fluxes in water‐limited ecosystems. In spite of the limitations inherent to the big‐leaf representation of the canopy, the equations are useful for predicting the influence of environmental factors in Mediterranean woodlands and for interpreting ecosystem exchange measurements.

Severe drought effects on ecosystem CO 2 and H 2 O fluxes at three Mediterranean evergreen sites: revision of current hypotheses? - Markus Reichstein; John D. Tenhunen; Olivier Roupsard; Jean‐marc Ourcival; Serge Rambal; Franco Miglietta; Alessandro Peressotti; Marco Pecchiari; Giampiero Tirone; Riccardo Valentini (Global Change Biology, 2002)
Eddy covariance and sapflow data from three Mediterranean ecosystems were analysed via top‐down approaches in conjunction with a mechanistic ecosystem gas‐exchange model to test current assumptions about drought effects on ecosystem respiration and canopy CO 2 /H 2 O exchange. The three sites include two nearly monospecific Quercus ilex L. forests – one on karstic limestone (Puéchabon), the other on fluvial sand with access to ground water (Castelporziano) – and a typical mixed macchia on limestone (Arca di Noè). Estimates of ecosystem respiration were derived from light response curves of net ecosystem CO 2 exchange. Subsequently, values of ecosystem gross carbon uptake were computed from eddy covariance CO 2 fluxes and estimates of ecosystem respiration as a function of soil temperature and moisture. Bulk canopy conductance was calculated by inversion of the Penman‐Monteith equation. In a top‐down analysis, it was shown that all three sites exhibit similar behaviour in terms of their overall response to drought. In contrast to common assumptions, at all sites ecosystem respiration revealed a decreasing temperature sensitivity ( Q 10 ) in response to drought. Soil temperature and soil water content explained 70–80% of the seasonal variability of ecosystem respiration. During the drought, light‐saturated ecosystem gross carbon uptake and day‐time averaged canopy conductance declined by up to 90%. These changes were closely related to soil water content. Ecosystem water‐use efficiency of gross carbon uptake decreased during the drought, regardless whether evapotranspiration from eddy covariance or transpiration from sapflow had been used for the calculation. We evidence that this clearly contrasts current models of canopy function which predict increasing ecosystem water‐use efficiency (WUE) during the drought. Four potential explanations to those results were identified (patchy stomatal closure, changes in physiological capacities of photosynthesis, decreases in mesophyll conductance for CO 2 , and photoinhibition), which will be tested in a forthcoming paper. It is suggested to incorporate the new findings into current biogeochemical models after further testing as this will improve estimates of climate change effects on (semi)arid ecosystems' carbon balances.

Simulating climate change impacts on fire frequency and vegetation dynamics in a Mediterranean‐type ecosystem - Florent Mouillot; Serge Rambal; Richard Joffre (Global Change Biology, 2002)
The impacts of climate change on Mediterranean‐type ecosystems may result from complex interactions between direct effects on water stress and subsequent modifications in flammability and fire regime leading to changes in standing biomass and plant species composition. We analysed these interrelations through a simulation approach combining scenarios of climate change developed from GCM results and a multispecies functional model for vegetation dynamics, SIERRA. A fire risk procedure based on weekly estimates of vegetation water stress has been implemented. Using climate data from 1960 to 1997, simulations of a typical maquis woodland community have been performed as baseline and compared with two climate scenarios: a change in the rainfall regime alone, and changes in both rainfall and air temperature. Climate changes are defined by an increase in temperature, particularly in summer, and a change in the rainfall pattern leading to a decrease in low rainfall events, and an increase in intense rainfall events. The results illustrate the lack of drastic changes in the succession process, but highlight modifications in the water budget and in the length of the drought periods. Water stress lower than expected regarding statistics on the current climate is simulated, emphasizing a long‐term new equilibrium of vegetation to summer drought but with a higher sensibility to rare events. Regarding fire frequency, climate changes tend to decrease the time interval between two successive fires from 20 to 16 years for the maquis shrubland and from 72 to 62 years in the forested stages. This increase in fire frequency leads to shrub‐dominated landscapes, which accentuates the yield of water by additional deep drainage and runoff.

Mediterranean terrestrial ecosystems: research priorities on global change effects - SANDRA LAVOREL; JOSEP CANADELL; SERGE RAMBAL; JAUME TERRADAS (Global Ecology and Biogeography, 1998)